Politics meets healthcare? Religious misinformation in India during the COVID-19 pandemic - Md.Sayeed Al-Zaman (Institut Teknologi Sepuluh Nopember, 2020)
India has recently become a hotspot of misinformation: the COVID-19 brings a new opportunity for the rumor-spreaders. Of various categories, religious misinformation seems harmful for both Indian society and public health. In this paper, therefore, I tried to sketch a few necessary aspects of religious misinformation in India during the COVID-19. From the previous literature and ongoing trend of Indian misinformation, I identified two important phenomena: (a) Though Muslims produce more spiritual misinformation, most of the religious misinformation targeting Muslims is inspired by Islamophobia; (b) misinformation that tries to champion Hinduism is more related to the contemporary political ideologies of India. I also tried to explain how religion as a political issue relates to public health